Engineering a genetically-encoded SHG chromophore by electrostatic targeting to the membrane - Jinno, Yuka; Shoda, Keiko; Rial-Verde, Emiliano; Yuste, Rafael; Miyawaki, Atsushi; Tsutsui, Hidekazu (Frontiers in Molecular Neuroscience, 2014)
Although second harmonic generation (SHG) microscopy provides unique imaging advantages for voltage imaging and other biological applications, genetically-encoded SHG chromophores remain relatively unexplored. SHG only arises from non-centrosymmetric media, so an anisotropic arrangement of chromophores is essential to provide strong SHG signals. Here, inspired by the mechanism by which K-Ras4B associates with plasma membranes, we sought to achieve asymmetric arrangements of chromophores at the membrane-cytoplasm interface using the fluorescent protein mVenus. After adding a farnesylation motif to the C-terminus of mVenus, nine amino acids composing its -barrel surface were replaced by lysine, forming an electrostatic patch. This protein (mVe9Knus-CVIM) was efficiently targeted to the plasma membrane in a geometrically defined manner and exhibited SHG in HEK293 cells. In agreement with its design, mVe9Knus-CVIM hyperpolarizability was oriented at a small angle (~7.3º) from the membrane normal. Genetically-encoded SHG chromophores could serve as a molecular platform for imaging membrane potential.